A 5′ RNA element promotes dengue virus RNA synthesis on a circular genome - Filomatori, C.V. (2006)
The mechanisms of RNA replication of plus-strand RNA viruses are still unclear. Here, we identified the first promoter element for RNA synthesis described in a flavivirus. Using dengue virus as a model, we found that the viral RdRp discriminates the viral RNA by specific recognition of a 5′ element named SLA. We demonstrated that RNA-RNA interactions between 5′ and 3′ end sequences of the viral genome enhance dengue virus RNA synthesis only in the presence of an intact SLA. We propose a novel mechanism for minus-strand RNA synthesis in which the viral polymerase binds SLA at the 5′ end of the genome and reaches the site of initiation at the 3′ end via long-range RNA-RNA interactions. These findings provide an explanation for the strict requirement of dengue virus genome cyclization during viral replication. © 2006 by Cold Spring Harbor Laboratory Press.